A Multidisciplinary Pediatric Neurology Clinic for Systematic Follow-up of Children with Neurologic Sequelae of COVID-19. (March 2023) - Patel, Payal B.; Patrick, Kristina E.; Benedetti, Giulia M.; Morgan, Lindsey A.; Bowen, Katherine S.; Wright, Jason N.; Wainwright, Mark S.
Clinical guidance on outpatient follow-up of children hospitalized with acute neurologic complications of SARS-CoV2 infection is needed. We describe the clinical infrastructure of our pediatric neurology post-Covid clinic, including our clinical evaluation and cognitive testing battery specific to this patient population, and a case series of our initial patient cohort. Our findings demonstrate cognitive sequelae in all 4 of our patients months following acute SARS-CoV2 infection with neurologic complications including acute disseminated encephalomyelitis, posterior reversible encephalopathy syndrome, viral encephalitis, and gait difficulties. Verbal and executive function domains were predominantly affected in our cohort, even in patients who did not endorse symptomatic or academic complaints at follow-up. Our recommendations include systematic clinical follow-up for children following hospitalization with SARS-CoV2 infection with a comprehensive cognitive battery to monitor for cognitive sequalae and to assist with developing an individualized education plan for the child as they return to school.